Animal structure and function - Starr, Cecile (Brooks/Cole/Thomson, 2004)
Extracted from the textbook 9th edition, in part, at least, to demonstrate the publisher's custom publishing capabilities. It is a full color text with index, glossary, questions & answers, but no bibliography